Análisis geomorfológico y morfométrico de lagunas de altura de los Andes Fueguinos mediante sistema de información geográfica e imágenes satelitales - San Martín, Cristina Natalia (2017)
Fuegian Andes are characterized by the development of glacial cirques and valleys. Many of these landforms are occupied by lakes. The objective of this study is to obtain a morphometric characterization of high altitude lakes of the Fuegian Andes, in the area between the south shore of the Lake Fagnano and the north shore of the Beagle Channel and the Argentina-Chile boundary at the W to 65º58?W at the E. Also the study presents the relationship between the morphometry, lithology and geomorphology emplacement and climatic characteristics. The identification, mapping and morphometric characterization of 187 lakes was carried out with a Geographic Information System (GIS) free and of open code QGIS 2.18.0 and with satellite imagery Landsat and Digital Elevation Models (DEM). The main orientation is to the SSE, like the major cirques in Fuegian Andes and South Hemisphere. The lakes have an area less than 1 km2 and the circular lakes are the predominant ones, there is no lithological control. The recognition of Little Ice Age moraines around them allowed assigning a relative age to 32 of the lakes; lakes near to cirque glaciers show their recent retreat.